Clinical application of the intersphincteric approach with internal incision combined with counter- drainage for deep perianal abscess - Jian-sheng Hu; Lin-mei Sun; Yang Wu; Xue-liang Yang; Wen Wang (BMC Gastroenterology)
Abstract Purpose This retrospective study evaluates the clinical efficacy of the Intersphincteric Approach with Internal Incision combined with Counter-Drainage (IAICD) for Deep Perianal Abscess (DPA), thereby providing a foundation for selecting optimal surgical treatment methods in clinical practice. Methods Using a retrospective cohort study design, we analyzed the clinical data of 120 patients who underwent inpatient surgical treatment for DPA at our hospital from January 2022 to June 2023. Of these, 57 patients underwent the IAICD (treatment group), while 63 patients received incision—drainage (control group). Clinical data from both groups were collected for statistical analysis. The primary outcomes measured were clinical efficacy, anal function scores and appearance scores. Secondary outcomes included postoperative pain, operation time, wound healing time and length of hospital stay. Results The treatment group had 52 cured cases, with a cure rate of 52/57 (91.2%), whereas the control group had 48 cured cases, with a cure rate of 48/63 (76.2%). The treatment group’s clinical efficacy was significantly better than the control group (P = 0.03). The operation time was longer in the treatment group compared to the control group (P < 0.01). There were no significant differences between the two groups in terms of anal function scores, appearance scores, postoperative pain, wound healing time and length of hospital stay (P > 0.05). Multivariate logistic regression analysis revealed that IAICD was a protective factor for the clinical efficacy of DPA patients (P = 0.01), While wound healing time and a history of perianal surgery were identified as independent risk factors associated with poor prognosis in patients with DPA (P = 0.039, P = 0.032). Conclusion For patients with DPA who have high expectations for minimizing postoperative recurrence, a comprehensive preoperative evaluation—including a history of prior perianal surgery—precise intraoperative localization of the internal opening, and meticulous postoperative wound care can collectively optimize clinical outcomes. The IAICD procedure not only preserves anal sphincter function but also effectively reduces the recurrence rate of postoperative abscesses or fistula formation.